PENINGKATAN KAPASITAS DAN KUALITAS PRODUKSI AMPIANG DI DESA SINAR JAYA KABUPATEN BANGKA - yuliyanto yuliyanto; Somawardi Somawardi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Ampiang is an authentic Bangka Belitung food made from tapioca, fish, water, salt and flavorings. Then in a round and thin shape with a diameter of 70 mm. You can find Ampiang bus at a warung or supermarket in Bangka Belitung. The objective of the Community Partnership Program (PKM) for the ampiang-making community groups is to improve the quality and production capacity of ampiang for partners. A survey has been conducted on ampiang making partners in Sinar Baru Sungailiat Village under the name